2000
DOI: 10.1021/la990472v
|View full text |Cite
|
Sign up to set email alerts
|

Protease Activity on an Immobilized Substrate Modified by Polymers:  Subtilisin BPN‘

Abstract: We describe the adsorption and catalytic behavior of the serine protease subtilisin BPN′ on controlled pore glass (CPG) beads with a short (aminopropyl) or a long (aminoalkyl CH2 > 12) chain covalent link separating the reporter peptide succinyl-alanine-alanine-proline-phenylalanine-p-nitroanilide (sAAPFpNA) from the surface. The propyl-linked sAAPFpNA modified glass surface (aminopropyl CPG:sAAPFpNA) showed a 2-fold increase in protease adsorption over an aminopropyl-glass surface. In contrast, the sAAPFpNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…However, as was observed for EK and EK-1, addition of enzyme even at large excess failed to hydrolyze the peptide substrate when bound to either microsphere or solution sensor (monitored by HPLC and fluorescence recovery experiments). It is possible that the enzyme is hindered from accessing the binding site on the peptide either through steric interactions with the polymer or by means of the irreversible adsorption of the enzyme to the hydrophobic polymer (21,22). The introduction of a poly(ethylene glycol) functional group between the biotin and the peptide substrate was expected to improve the situation in one of the following ways: increase the distance between the cleavage site and the polymer to prevent steric hindrance to approach by the enzyme or reduce the hydrophobicity and, thus, reduce adsorption of enzyme to the polymer (23).…”
Section: Resultsmentioning
confidence: 99%
“…However, as was observed for EK and EK-1, addition of enzyme even at large excess failed to hydrolyze the peptide substrate when bound to either microsphere or solution sensor (monitored by HPLC and fluorescence recovery experiments). It is possible that the enzyme is hindered from accessing the binding site on the peptide either through steric interactions with the polymer or by means of the irreversible adsorption of the enzyme to the hydrophobic polymer (21,22). The introduction of a poly(ethylene glycol) functional group between the biotin and the peptide substrate was expected to improve the situation in one of the following ways: increase the distance between the cleavage site and the polymer to prevent steric hindrance to approach by the enzyme or reduce the hydrophobicity and, thus, reduce adsorption of enzyme to the polymer (23).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the immobilization of the substrates for the determination of the enzymic activity has not met a wide implementation yet. With the advent of micro-array technology, a large variety of new applications of enzyme action on solid-phase supported substrates have been rapidly developed [16][17][18][19][20]. Substrate immobilization on solid surfaces is becoming increasingly important, especially in the case of photosynthetic materials which often present a relatively short active lifetime limiting their effective use [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Yoshitake et al [ 6 ] in their studies have shown that the captured transition metal ions on amino-functionalized silica act as adsorption centers for arsenate ions. Surface-functionalized silica particles have found applications in catalysis [ 7 - 9 ], sensors [ 7 , 10 ], and protein immobilization [ 11 , 12 ]. Also, functional groups have been incorporated into silicate surfaces to facilitate molecular imprinting of those surfaces to form highly specific biomimetic catalytic or adsorbent materials [ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%